Socjologia wizualna w praktyce: empiryczne przykłady współpracy socjologów z fotografami = Visual sociology in practice: empirical examples of the cooperation between the sociologists and photographers - Rogowski, Łukasz (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article shows chosen ways of cooperation between sociology and photography. The starting point is the indication that these both spheres of activity have similar roots connected with the values present in modern society. There follows a presentation of general frames of the cooperation in question, executed in the context of visual sociology understood as a way to perform sociology that trusts the images.
Keywords: socjologia wizualna; socjologia; fotografie